A design strategy for aGST-GST-VO2-Ag based tunable thermal emitter. (1st April 2023) - Song, Rumeng; Zhang, Yuzhi; Zhang, Yan; Ma, Jiayu; Wu, Lingnan; Song, Lixin
Abstract: This work demonstrates a mid-infrared emitter based on Ge8 Sb2 Te11 (GST) and VO2 . The results show that GST and VO2 have contrasting optical properties, which enable the emitter to reach a modulation depth of up to 82.5%. Continuous modulation of the resonant peak in the broad spectral range of 6.3–9.2 μ m was achieved by modulating the crystallization ratio of the top GST layer. The structure can reach a controllable average emissivity of 11.5%–83.4% within 5–8 μ m, 2.0%–19.0% at 8–14 μ m, and 6.0%–47.3% at 3–5 μ m, which is close to an ideal thermal emitter performance. Moreover, the structure is insensitive to both incident angle and polarization.